N-Acetyltransferase 2 gene polymorphism in a group of senile dementia patients in Shanghai suburb - GUO Wei-chao; LIN Guo-fang; ZHA Yong-lin; LOU Ke-jian; MA Qing-wen; SHEN Jian-hua (Acta Pharmacologica Sinica; Vol 25, No 9 (September 2004): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the possible association of hereditary polymorphism of N-acetyltransferase 2 (NAT2) gene with the susceptibility towards senile dementia in farmer population of Shanghai suburb. METHODS: NAT2 gene genotyping was performed at 7 major polymorphic loci (G191A, C282T, T341C, C481T, G590A, A803G, and G857A) with a polymerase chain reaction-based restriction fragment length polymorphism based procedure in 2 groups of farmer subjects in Shanghai suburb. A group of 51 diagnosed dementia patients [comprising 29 sporadic Alzheimer disease (AD) patients and 22 sporadic vascular dementia (VD) patients] and a group of 112 healthy individuals were in the same area. RESULTS: The homogenous rapid genotypes (R/R, including*4/*4, *13 /*13, and *4/*13) was found over-present in both groups of patients, compared with healthy individuals, for all farmer dementia patients, 52.9 % vs 33.0 %, P=0.016, OR (95 % CI): 2.28(1.16-4.48); for AD group only, 51.7 % vs 33.0 %, P=0.063, OR (95 % CI): 2.18 (0.95-4.97); for VD group 54.5 % vs 33.0 %, P=0.055, OR (95 % CI): 2.43 (0.96-2.43). The significant frequency difference of genotype *4/*7B between farmer dementia patients and healthy individuals, and that of solo-alleles *13, and *7B were observed between the healthy individuals and both groups of dementia patients. CONCLUSION: Our data suggest the involvement of various NAT2 rapid-acetylating genotypes in the individual susceptibility to senile dementia. Variant genotypes of NAT2 might serve as a hereditary risk factor for AD and VD in Chinese population.